Inovasi Pelaksanaan Posyandu Selama Masa Pandemi Covid-19: Studi Kualitatif di Wilayah Kerja Puskesmas Campalagian - Najdah Najdah; Nurbaya Nurbaya (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Posyandu cadres play an important role in assisting Public Health Center in carrying out the functions of implementing health efforts and have a strategic position to prevent stunting problems, especially in time the Covid-19 pandemic. This study aimed to describe the implementation of Integrated Health Post (Posyandu) in the working area of ​​the Campalagian Health Center during the Covid-19 pandemic in 2020. This study qualitative used a phenomenology approach which was carried out in the working area of ​​the Campalagian Health Center in July - September 2020. A total of 10 Posyandu cadres were the main informants. Data were collected through in-depth interviews for 60 – 90 minutes conducted at the homes of Posyandu cadres while still paying attention to health protocols. Cadres did not carry out Posyandu in April and May 2020 following local government regulations or in certain months when there was an increase in cases of Covid-19 in the area. In implementing the Posyandu during the pandemic, cadres made several innovations such as setting up emergency handwashing facilities, arranging visit schedules, and the distance of waiting chairs at the Posyandu, requiring them to bring their own sharoong from home for weighing toddlers and disinfecting the Posyandu room. In conclusion, cadres make innovations in the implementation of Posyandu during the pandemic such as preparing emergency hand washing facilities, arranging visit schedules and waiting chair spacing at Posyandu, requiring them to bring their own gloves and disinfecting the Posyandu room. The implementation of Posyandu during the Covid-19 pandemic can prevent an increase in nutritional problems in mothers and stunting problems in toddlers. Therefore, the local government is expected to support the implementation of Posyandu routinely such as ensuring the availability of PPE for posyandu cadres, mothers and toddlers. So that Posyandu can still be implemented while still observing health protocols.